Mortality in patients with permanent hypoparathyroidism after total thyroidectomy. Issue 10 (17th April 2018) - Almquist, M.; Ivarsson, K.; Nordenström, E.; Bergenfelz, A.
Abstract : Background: Permanent hypoparathyroidism remains the most common adverse outcome after total thyroidectomy, but long‐term effects of hypoparathyroidism are unknown. The aim was to investigate mortality in patients with permanent hypoparathyroidism after total thyroidectomy. Methods: Data from the Scandinavian Quality Register for Thyroid, Parathyroid and Adrenal Surgery were linked with the Swedish National Prescription Register for Pharmaceuticals and the Swedish National Inpatient Register. Patients who underwent total thyroidectomy between 1 July 2005 and 30 June 2014 for benign thyroid disease, and who used active vitamin D for at least 6 months after surgery, were classified as having permanent hypoparathyroidism and included in the study cohort. Risk of death was assessed using Cox regression analysis, adjusting for age, sex, thyrotoxicosis and co‐morbidity. Results: There were 4899 patients, with a mean(s.d.) age of 46·3(15·8) years; 83·1 per cent were women, and 2932 patients (59·8 per cent) had thyrotoxicosis. In all, 246 patients (5·2 per cent) were classified as having permanent hypoparathyroidism. Mean(s.d.) follow‐up was 4·4(2·4) years, and 109 patients (2·2 per cent) died during follow‐up. Compared with patients without permanent hypoparathyroidism, the risk of death was significantly higher among patients with permanent hypoparathyroidism after total thyroidectomy (adjusted hazard ratio 2·09, 95 per cent c.i. 1·04 to 4·20). Conclusion: Permanent hypoparathyroidism after total thyroidectomy for benign disease is common and associated with an increased risk of death. Abstract : Higher than expected